2010
DOI: 10.1007/s10865-010-9290-8
|View full text |Cite
|
Sign up to set email alerts
|

Religious coping and hospital admissions among adults with sickle cell disease

Abstract: Although a well-established literature implicates religiosity as a central element of the African American experience, little is known about how individuals from this group utilize religion to cope with specific health-related stressors. The present study examined the relation between religious coping and hospital admissions among a cohort of 95 adults with sickle cell disease—a genetic blood disorder that, in the United States, primarily affects people of African ancestry. Multiple regression analyses indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Prior research suggests that religious involvement is positively associated with health behaviors and outcomes among African Americans (Bediako et al, 2011; Holt, Clark, & Roth, 2014; Waldron-Perrine et al, 2011). Bediako et al (2011) found that greater positive religious coping was associated with fewer hospital admissions among African Americans with sickle-cell disease.…”
Section: Religion’s Importance To African Americans Perceptions Of Hementioning
confidence: 99%
“…Prior research suggests that religious involvement is positively associated with health behaviors and outcomes among African Americans (Bediako et al, 2011; Holt, Clark, & Roth, 2014; Waldron-Perrine et al, 2011). Bediako et al (2011) found that greater positive religious coping was associated with fewer hospital admissions among African Americans with sickle-cell disease.…”
Section: Religion’s Importance To African Americans Perceptions Of Hementioning
confidence: 99%
“…A short form of this nature has been used in a previous study on the sickle-cell population (Bediako et al, 2011); and further indicates that the revised scale is an adequate means of assessing religious coping, as it demonstrated moderate coefficient alpha scores of .72 and .79 for the positive and negative scales, respectively. These figures were derived after a principal component analysis utilising orthogonal varimax rotation was conducted on six items of religious coping (three positive and three negative), and was found to be adequate as the Kaiser-Meyer-Olkin index was .68, which is within the normal range for scores.…”
Section: Disease Severitymentioning
confidence: 99%
“…This allowed for a positive religious scale score (ranging from 3 to 12) and a negative or "religious struggle" scale score (ranging from 2 to 8) to be established. These scores were further interpreted as high scores indicating an endorsement of the various scales (Bediako et al, 2011).…”
Section: Disease Severitymentioning
confidence: 99%
See 2 more Smart Citations